EARLY PHOTOGRAPHY IN VIETNAM - Bennett, Terry. Link ([S.l.])
1 online resource
Keywords: Early Photography in Vietnam is a fascinating and outstanding pictorial record of photography in Vietnam during the century of French rule. In more than 500 photographs, many published here for the first time, the volume records Vietnam's capture and occupation by the French, the wide-ranging ethnicities and cultures of Vietnam, the country's fierce resistance to foreign rule, leading to the reassertion of its own identity and subsequent independence. This benchmark volume also includes a chronology of photography (1845-1954), an index of more than 240 photographers and studios in the same period, appendixes focusing on postcards, royal photographic portraits, Cartes de Visite and Cabinet Cards, as well as a select bibliography and list of illustrations.